FROM FIASP TO TRURAPI: CONVERSION IN INSULIN ASPART PRESCRIBING IN THE UNITED KINGDOM AND THE IMPACT OF DELIVERY-DEVICE PREFERENCES - Heba M. Attash (Global Journal of Public Health Medicine, 2026)
Introduction: In England, NovoRapid® dominated the rapid-acting insulin aspart market until 2017, when Fiasp® (next-generation fast-acting aspart) was launched, followed by Trurapi® (similar to NovoRapid®) after UK approval in 2021 (European marketing authorization 2020). Methods: Prescribing information from NHS primary care data was aggregated and adjusted to defined daily doses (DDD, 40 IU) between 2008 and 2024. Segmented regression models with two intervention points (Fiasp® Q1 2017, Trurapi® Q4 2021) were estimated, with separate analyses by device (pre-filled pens, cartridges, vials). Results: NovoRapid® continued to increase until 2017, when the growth slowed after the introduction of Fiasp. Fiasp® grew rapidly after launch and was approximately 1.25 million DDDs (95% CI 0.42 to 2.08 million) above the counterfactual two years after Trurapi® was introduced (p < 0.001). The uptake of Trurapi® was typical of biosimilar products, with approximately 5.4% of the market share by Q4 2024 (95% CI 4.8% to 7.2%). Adoption was greater in pens and cartridges than in vials, reflecting prescribers’ and patients’ familiarity with the originator products' pen platforms. Conclusions: In 17 years, the England insulin aspart market was transformed with successive product launches. In addition to clinical comparability, familiarity with the device and the timing in the market lifecycle were key factors in adoption. Monitoring utilization at both brand and device level may help policymakers and prescribers with biosimilar integration and ensure patient confidence.